The implications of a health promotion program on the knowledge and practice of automotive workers exposed to solvent - Ruslan, Rumaizah; Hashim, Zailina; Ismail, Ismi Arif; Lin, Naing; Nordin, Rusli (Science Publications, 2010)
Problem statement: An in-house health promotion program aimed at promoting safety and health awareness when handling organic solvents at the workplace was carried out and its effectiveness was evaluated by comparing the Knowledge, Attitude and Practices (KAP) scores at the pre and post-intervention phase.